2019
DOI: 10.1029/2019jf005193
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Flow Asymmetry and Discharge of Lateral Tributaries Drive the Evolution of a Microtidal Meander in the Venice Lagoon (Italy)

Abstract: Tidal landscapes are extensively characterized by the presence of meandering channels, the latter being important for the ecomorphodynamic evolution of these environments. It remains unclear whether changes in the relative strength of maximum flood and ebb currents (i.e., tidal flow asymmetries), together with the widespread presence of lateral tributaries, cause tidal meanders to evolve differently from their fluvial relatives. Here, we investigate the evolution of a meandering channel in the Venice Lagoon (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 88 publications
8
52
0
Order By: Relevance
“…Nidzieko (2010) investigated three California estuaries with negative tidal asymmetries imposed in their mouths and demonstrated that such asymmetries increase or decrease (according to the estuarine morphology) as the tide propagates landward and therefore affects several internal processes. Similarly, Ferrarin et al (2015) and Finotello et al (2019) point out that the inlet region and the main channels of Venice lagoon were dominated by the negative tidal asymmetry of the North Adriatic Sea. Ferrarin et al (2015) obtained the annual value of γ 1 in the period 1976-2014 with the data of a tide gauge station located 15 km offshore from the Venice lagoon inlets and verified that γ 1 oscillated around an average value of −0.09, coinciding with the results of the classification carried out in this study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nidzieko (2010) investigated three California estuaries with negative tidal asymmetries imposed in their mouths and demonstrated that such asymmetries increase or decrease (according to the estuarine morphology) as the tide propagates landward and therefore affects several internal processes. Similarly, Ferrarin et al (2015) and Finotello et al (2019) point out that the inlet region and the main channels of Venice lagoon were dominated by the negative tidal asymmetry of the North Adriatic Sea. Ferrarin et al (2015) obtained the annual value of γ 1 in the period 1976-2014 with the data of a tide gauge station located 15 km offshore from the Venice lagoon inlets and verified that γ 1 oscillated around an average value of −0.09, coinciding with the results of the classification carried out in this study.…”
Section: Discussionmentioning
confidence: 93%
“…(2015) and Finotello et al. (2019) point out that the inlet region and the main channels of Venice lagoon were dominated by the negative tidal asymmetry of the North Adriatic Sea. Ferrarin et al.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that morphological changes due to intensive human interventions are widespread and may cause significant alternations in water levels and related tidal hydrodynamics (Jay, 1991; Vriend, 1991; Chernetsky, Schuttelaars, & Talke, 2010; Zhang et al, 2010; Finotello et al, 2019). Based on the morphological metrics summarized in Table 3, we observed that the net sedimentation rate in Lingdingyang Bay switched from positive to negative in 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal–spatial tidal forcing affects not only the transport of sediments, nutrients, and contaminants (Falcão, Santos, Drago, Serpa, & Monteiro, 2009; Bonaldo et al, 2014) in estuaries but also salt intrusion and storm surge propagation (Zhang, Savenije, Wu, Kong, & Zhu, 2011; Zhang, Savenije, Chen, & Mao, 2012; Li, Zhu, Wu, & Guo, 2014). In recent decades, intensive human activities (e.g., dredging for navigation, sand excavation, and land reclamation) have dramatically changed the morphology of many estuaries and, have caused the erosion of estuarine saltmarshes (Bendoni et al, 2016; Francalanci, Bendoni, Rinaldi, & Solari, 2013; Tommasini, Carniello, Ghinassi, Roner, & D'Alpaos, 2019) and altered the tidal regimes and hydrodynamics (Zhang et al, 2017; Mei et al, 2018; Wu et al, 2018; Zhang et al, 2018; Finotello Canestrelli, Carniello, Ghinassi, & D'Alpaos, 2019). For these reasons, the response of tidal forcing to human activities has attracted worldwide research attention.…”
Section: Introductionmentioning
confidence: 99%
“…The present‐day configuration of the lagoon is characterized by the presence of sparse salt marshes (Finotello et al ., 2020b) undergoing rapid erosion in the last two centuries (D’Alpaos, 2010; Tommasini et al ., 2019), wide subtidal platforms, and tidal flats that are cut by intertidal and subtidal channels (Finotello et al. , 2019; Ghinassi et al. , 2019) (Fig.…”
Section: Geological Settingmentioning
confidence: 99%